Study of individual pulses at the Antarctic high-altitude neutron monitor DOMC - Similä, Markus; Poluianov, Stepan; Usoskin, Ilya (2021)
A pair of neutron monitors (NMs) is installed on the high Central Antarctic plateau, at the Concordia station (3200 m altitude) and measures the nucleonic component of nucleonic-muon-electromagnetic cascades in- duced by high-energy cosmic rays in the atmosphere. The installation includes two NMs: DOMC, a standard mini-NM, and a bare (lead-free) DOMB NM. The newly installed data acquisition (DAQ) system records in- dividual pulses corresponding to mostly neutrons in the detector’s counting tube. Here we analyze different types of pulses and study the distribution of the waiting times between individual pulses as well as the pulse height, recorded by the DOMC NM during a quiet period of January 2020. The distribution appears double- peaked with peaks corresponding to the frequency of individual atmospheric cascades and the intra-cascade variability, respectively. We discuss also the nature of different components contributing to the pulses and se - paration of the signal from noise. It is shown that the waiting-time distribution has distinguished timescales, >30 ms defined by the cosmic-ray induced atmospheric cascades, and <10 ms reflecting the intra-cascade variability. The new DAQ system allows one to study the development of the atmospheric cascade.